Sexualidade: percepções de mulheres adolescentes - Gondim, Maria Fátima Barbosa (2000)
The adolescence during the second decade of human being?s lífe is a stage constitutede by deep biopsichosocial changes. This study have had as objectives identifying the perception of the adolescence about sexuality; analising the construction of the concept of sexuality starting from the reports given by the adolescents and identifying the expectations of the adolescents about the exercise of their sexuality. This descriptive-explora to ry work was accomplisehd at NAMI (Núcleo de Atenção Médica Integrada - Integrated Medicai Atention Center); from august until september 1999, with the participado n of 30 adolescents who live at Favela do Dendê, Fortaleza, Ceará, Brazil, and are clients at the Gyneco-obstetrics Ambulatory. The data have been colected by meanings of semi-structured interview and observation, and to organize the Information, weVe used the Thematic Analisis method proposed by Minayo (1993), which allowed us to characterize these adolescents, stablishingthe categories: Noticingthe sexuality; Discovering and constracting the concept of sexuality and Expectations about the practice os the sexuality* The analisis were based on the thoughts of Foucault and Leininger, and other author. The interview lead us to know what concept the adolescents had about sexuality, through the exposition of their ideas and understanding is Sex. The ideas they had about sexuality, in the most part were linked to Sex as physical and genital, although they don’t know their bodies and the process that envolves afetivity and emotional acts. They’ve made their concepts based on self-cliscoveiy, through their partners or even through the media, and they have received little Information in what concern school and family. Besicles showing a low levei of aspiration, they don’t know theirselves as women, citizens who have the right of living their sexuality not only to be a reproductor and mother, and clorrt comprehend the sexuality as someching that complete their meaning of existence s human beings. WeVe observed that the concepts and ideas about sexuality are macle up based in their social concepts, making them vulnerable to violence, tíie STD, beginning of a precocious sexual liffe and a non-plannecl pregnancy. To get o ver these problems it’s necessary the adoption of multiprofessional work close to the families, schools, community and health Services.